Weak Tectono-Magmatic Relationships along an Obliquely Convergent Plate Boundary: Sumatra, Indonesia - Acocella, Valerio; Bellier, Olivier; Sandri, Laura; Sébrier, Michel; Pramumijoyo, Subagyo (Frontiers in Earth Science, 2018)
The tectono-magmatic relationships along obliquely convergent plate boundaries, where strain partitioning promotes strike-slip structures along the volcanic arc, are poorly known. Here it is unclear if and, in case, how the strike-slip structures control volcanic processes, distribution and size. To better define the possible tectono-magmatic relationships along strike-slip arcs, we merge available information on the case study of Sumatra (Indonesia) with field structural data. The Sumatra arc (entire volcanic belt) consists of 48 active volcanoes. Of these, 46% lie within 10 km from the dextral Great Sumatra Fault (GSF), which carries most horizontal displacement on the overriding plate, whereas 27% lie at >20 km from the GSF. Among the volcanoes at <10 km from GSF, 48% show a possible structural relation to the GSF, whereas only 28% show a clear structural relation, lying in pull-aparts or releasing bends; these localized areas of transtension (local extensional zone) do not develop magmatic segments. There is no relation between the GSF along-strike slip rate variations and the volcanic productivity. The preferred N30°-N40°E volcano alignment and elongation are subparallel to the convergence vector or to the GSF. The structural field data, collected in the central and southern GSF, show, in addition to the dextral motions along NW-SE to N-S striking faults, also normal motions (extending WNW-ESE or NE-SW), suggesting local reactivations of the GSF. Overall, the collected data suggest a limited tectonic control on arc volcanism. The tectonic control is mostly expressed by the mean depth of the slab surface below the volcanoes (130±20 km) and, subordinately, local extension along the GSF. The latter, when WNW-ESE oriented (more common), may be associated with the overall tectonic convergence, as suggested by the structural data; conversely, when NE-SW oriented (less common), the extension may result from co- and post-seismic arc normal extension, as supported by the 2004 mega-earthquake measurements. Overall, the strike-slip arc of Sumatra has intermediate features between those of extensional and contractional arcs.